The Low Carbon City Development Program Guidebook : A Systems Approach to Low Carbon Development in Cities - World Bank (World Bank, Washington, DC, 2015)
According to the United Nations population fund, the world is undergoing the largest wave of urban growth in history, with more people now living in cities than in rural areas. Cities are also responsible for a high proportion of global carbon emissions, which are the main driver of anthropogenic climate change. By taking the lead on low carbon development, cities have the opportunity to engage in an important dialogue about sustainable development, directly address local issues, and contribute to the reduction of greenhouse gas (GHG) emissions. Low carbon development strategies allow cities to position themselves as major players in climate change mitigation, as well as set an example for the development of national emission reduction policies. The systematic approach offered by a low carbon city development program (LCCDP) enables a city to overcome the barriers faced in single project implementation and pursue an integrated low carbon pathway. It provides a common framework to identify, implement, and measure low carbon interventions that will not only contribute to lower emissions, but will also address urban development needs. The LCCDP guidebook helps orient cities to design and implement an LCCDP that complies with the LCCDP assessment protocol, which is a new protocol based on existing, internationally recognized standards for systems design, and GHG accounting. The LCCDP assessment protocol consists of a set of standardized requirements developed to ensure that LCCDPs will achieve their targets and objectives when implemented. Thus the guidebook aims to assist the reader through the process of designing and implementing an LCCDP.